Constructing Z-scheme 1D/2D heterojunction of ZnIn2S4 nanosheets decorated WO3 nanorods to enhance Cr(VI) photocatalytic reduction and rhodamine B degradation. (February 2023) - Lian, Xinyi; Huang, Zongyi; Zhang, Yuqi; Chen, Zhou; Meidl, Peter; Yi, Xiaodong; Xu, Baile
Abstract: Photocatalysis has been vastly employed as a feasible and efficient strategy for the removal of environmental pollutants. In this study, a well-designed core-shell heterojunction of WO3 decorated with ZnIn2 S4 nanosheets were fabricated under mild in-situ conditions, and fabricated processes were systematically investigated with different fabrication durations. The coupling of WO3 and ZnIn2 S4 (ZIS) resulted in a Z-scheme mechanism for charge carrier transfer, holding the respective redox capacity. The as-prepared 1D/2D WO3 @ZIS heterostructure displayed the highest removal efficiency within 30 min for 25 mg L −1 Cr(VI), 89.3 and 29.7 times higher than pure WO3 and ZnIn2 S4 . 1D/2D WO3 @ZIS remained excellently stable after 5 cycling experiments. Moreover, 40 mg L −1 RhB could be degraded within 50 min. The broad and short photogenerated electron transportation path is guaranteed by the 1D/2D and Z-scheme charge separation mechanism. It efficiently prevented photo-generated charge carriers from recombination, resulting in a longer carrier lifespan and better photocurrent responses than that of pure ones. This photocatalytic system showed promising results and also provides a framework for an efficient system for photocatalysis with potential for environmental application. Graphical abstract: Image 1 Highlights: A novel 1D/2D bifunctional core-shell heterojunction of WO3 @ZIS was fabricated. The photocatalyst efficiently reduced 25 mg L −1 Cr(VI) in 30 min. Reduction efficiency of WO3 @ZIS to Cr(VI) was 89.3 and 29.7 times greater than pure WO3 and ZnIn2 S4. Photocatalytic degradation of Rhodamine B at 40 mg L −1 was achieved in 50 min. The coupling of WO3 and ZnIn2 S4 resulted in the better photocarrier separation efficiency.